2014
DOI: 10.1097/ico.0000000000000036
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mean Corneal Power Change After Pterygium Excision

Abstract: Pterygium exceeding a length of 2.0 mm induced a significant corneal power change after surgery. The mean K predicted from the regression analysis could be used as an approximation for a simultaneous pterygium and cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
5
18
0
Order By: Relevance
“…These contractile features mimic the clinical presentation of pterygium, which leads to significant astigmatism with an elastic nature. 48 In the current study, mTOR inhibition with Torin2 substantially blocked the TGF-b-induced contractile phenotype in pterygium myofibroblasts. However, it did not affect phosphorylation of SMAD proteins, which is a canonical downstream phenomenon of signaling through TGF-b receptors.…”
Section: Discussionsupporting
confidence: 53%
“…These contractile features mimic the clinical presentation of pterygium, which leads to significant astigmatism with an elastic nature. 48 In the current study, mTOR inhibition with Torin2 substantially blocked the TGF-b-induced contractile phenotype in pterygium myofibroblasts. However, it did not affect phosphorylation of SMAD proteins, which is a canonical downstream phenomenon of signaling through TGF-b receptors.…”
Section: Discussionsupporting
confidence: 53%
“…17 Induced astigmatism is generally characterized as with-the-rule astigmatism that is hemimeridional on the side of the pterygium resulting from localized flattening of the cornea. 3,4,[6][7][8]10,13,17,25 It is postulated that contractile elements within the pterygium exert tractional force and mechanically distort and flatten the cornea. 26 Therefore, it can be inferred that the pterygium with a greater tractional force or larger amount of contractile tissues can induce more severe PIA.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important for making decisions regarding pterygium surgery and patient selection, as this is often difficult because of the high rate of recurrence after pterygium surgery. 11,12 Although several studies showed significant correlation between the length, width, or area of pterygium and PIA, [4][5][6]9,[13][14][15][16][17][18] there are still controversies between the results of these studies. Moreover, influence of factors other than these factors, such as, density of vascularity or fibrous tissue that reflect tractional force exerted from pterygium, has never been investigated.…”
mentioning
confidence: 99%
“…Tomidokoro et al 5 found a correlation between the percentage of pterygium extension onto the cornea (%) and induced corneal astigmatism. Mohammad-Salih et al 7 , Kim et al 10 and Han et al 13 paid attention to the pterygium length, width and area and found that PIA was associated with these parameters. Our study found out that the pterygium surface area was an independent predictor of PIA (P < 0.001), which was in consistency with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cataract surgeons must understand the influences of pterygium on corneal astigmatism and the IOL power calculation before deciding on appropriate surgical strategies. Previous studies have indicated a significant correlation between pterygium-induced astigmatism (PIA) and its size, and the predicted IOL power would increase in eyes with a pterygium 5,[7][8][9][10][11] .…”
mentioning
confidence: 99%